X-ray semiotics of endocrine ophthalmopathy. Part 1. Extraocular muscles and orbital cellular tissue - O. Yu. Yatsenko; I. E. Tyurin (Вестник рентгенологии и радиологии, 2016)
Objective: to examine the state of the extraocular muscles and orbital cellular tissue of patients with different clinical forms of endocrine ophthalmopathy.Material and methods. The study involved 294 patients (559 orbits) with endocrine ophthalmopathy. In 87 of them (174 orbits), thyrotoxic exophthalmos was diagnosed, in 172 (343 orbits) – edematous exophthalmos (with myogenic type in 30 patients, lipogenic type in 46, mixed type in 96 patients), in 35 patients (42 orbits) – endocrine myopathy.Results. The article presents the volumes of extraocular muscles and orbital cellular tissue in patients with different forms of endocrine ophthalmopathy. The density of the muscles and orbital cellular tissue was studied in details in those groups of patients. The results show that increase of extraocular muscles volume is greater than increase of orbital cellular tissue volume, and have specific features for each form of endocrine ophthalmopathy.Conclusion. We detected significant quantitative differences in orbit soft tissue volume in patients with endocrine ophthalmopathy. That confirms the feasibility of allocating of three forms of endocrine ophthalmopathy and explains its variative clinical presentations.